Are Couples More Satisfied When They Match in Sexual Desire? New Insights From Response Surface Analyses. Issue 4 (May 2021) - Kim, James J.; Muise, Amy; Barranti, Max; Mark, Kristen P.; Rosen, Natalie O.; Harasymchuk, Cheryl; Impett, Emily
While sexual frequency and satisfaction are strong contributors to the quality and longevity of romantic relationships and overall well-being, mismatches in sexual desire between partners are common and have been linked with poorer satisfaction. Previous findings linking mismatches in desire with poorer relationship and sexual outcomes have typically been derived using difference scores, an approach that does not account for partners' overall levels of desire. In a sample of 366 couples, we investigated whether partners who match in desire are more satisfied than desire-discrepant couples. Results of dyadic response surface analyses provided no support for a unique matching effect. Higher desire rather than matching in desire between partners predicted relationship and sexual satisfaction. These findings shed new light on whether the correspondence between partners' levels of sexual desire is associated with satisfaction and suggest the need to focus on sustaining desire and successfully navigating differences rather than promoting matching in desire.